Content Analysis of General Science Text Book for 8th Grade - Zubair Ahmad Shah, Nasir Mahmood, Javed Hassan Akhtar, (PJE, 2023)
General Science textbooks have integrated contents of Biology, Chemistry, Physics and; Earth and Space, demand special attention of curriculum developers. This study aimed to explore the contents of General Science textbook of 8th grade taught in government and private schools of Punjab province. This qualitative nature research was conducted through content analysis design. T